Seismic Analysis and Design of G+4 Residential Building by Equivalent Static Analysis Method by Using STAAD Pro - Madireddy Satyanarayana, Tiriveedhi Sai Krishna, Gottipati Manidhar, B. Raghava Maheedhar (International Journal of Advanced Science and Technology, 2020)
There are numerous structures that have essential basic framework, which don’t meet the current seismic necessities and endure broad harm during the tremor. Thebuiliding structures at Vijayawada locale were planned by essential basic framework and the explanation for this is Vijayawada lies in ZONE III of Seismic Zone Map of 2002 for example as indicated by Seismic Zone Map of IS: 1893-2002, which says the area is moderate harm chance zone. This is the explanation the structures which don’t satisfy the prerequisites of seismic plan, may endure broad harm or breakdown whenever shaken by a serious ground movement. The seismic assessment mirrors the seismic limit of tremor defenseless structures for the future use. As indicated by the Seismic Zoning Map of IS: 1893-2002, India is partitioned into four zones based on seismic exercises. They are Zone II, Zone III, Zone IV and Zone V. Vijayawada lies in Zone III. In this examination the structure has been broke down and furthermore gave support subtleties of ordinary structure, Building with seismic burdens and structures with seismic loads and shear walls